Assessing the sustainable municipal solid waste (MSW) to electricity generation potentials in selected Pacific Small Island Developing States (PSIDS). (1st March 2020) - Joseph, Lionel P.; Prasad, Ramendra
Abstract: The Pacific Small Island Developing States (PSIDS) are largely reliant on fossil fuels for electricity generations and this dependency makes these Island States immensely vulnerable to global fuel price volatility since the excess outflow of money on fuel imports not only affects the economic growth but also hinders the sustainable development. Additionally, waste management in these small countries is economically and environmentally expensive and mostly dumped in open/closed-dumps and landfills which decompose and releases notorious greenhouse gases (i.e., methane and carbon dioxide, etc.). Amalgamating these two disparate issues, this study aims to find a mutual solution by exploring the feasibility of waste-to-energy (WtE) potentials via different technologies at the selected sites. Using the population and per capita waste generation data of fifteen selected sites of eight PSIDS, a waste profile of each site is evaluated. Then, the waste generation over the projected 20 years is used to determine the electricity generation potential of each site under the proposed alternative scenarios (i.e., 2 – landfill gas to energy (LFGTE) technology, 3 – mass-burn incineration, 4 – hybrid mechanical-biological treated (MBT) anaerobic digestion (AD) and LFGTE technology, and 5 – hybrid MBT-AD and refuse-derived fuel (RDF) incineration). These four scenarios (2–5) are compared to the Business-as-Usual case denoted as scenario 1. To test the economic viability, the Net Present Value, Levelized Cost of Energy, and Payback Period of each site is ascertained. Further economic benefits are assessed through the recycling of materials including plastics (under scenario 4 only), glass, and metals (under all scenarios). Emissions and energy consumption of each scenario are analysed using the Waste Reduction Model (WARM). The outcome of this study revealed that scenario 3 offers the greatest potential in terms of electricity generation, at Port Moresby (PNG1), Papua New Guinea site having the highest potential (i.e., 78.86 GWh) and Kosrae (FSM4), Federated States of Micronesia has the lowest generation potential of only 92.86 MWh. This scenario 3 (mass-burn incineration) was also supported by the economic assessment. It was also found that recycling brought in additional economic benefits and also helped offset CO2 -equivalent emissions and contributed towards energy savings. Multi-level multi-criteria decision analysis (ML-MCDA) was performed to select the most viable waste management alternative based on technical, economic, environmental, and stakeholder preferences. The priorities assigned to the respective scenarios for all fifteen sites were as such: scenario 3 > scenario 5 > scenario 4 > scenario 2 > scenario 1. Highlights: Four WtE generation scenarios were benchmarked against the baseline scenario. Economic feasibility of waste-to-energy generation has been analysed. Emissions and energy used under respective scenarios were evaluated. Energy recovery and recycling offers a good waste reduction alternative. Multi-criteria analysis showed that incineration technique is most preferable.